Security and Privacy Challenges in MHN - Zhang, Kuan; Shen, Xuemin (Sherman) (Security and Privacy for Mobile Healthcare Networks, 2015)
The objective of the monograph is to investigate security and privacy in MHNs. This chapter first present the general security and privacy requirements in MHNs. Then, we discuss several unique security and privacy challenges for MHNs.